72.1k views
1 vote
You were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation. 2x-7y=4 3x+y=-17

User Miller
by
5.9k points

1 Answer

5 votes

Answer:

2(-17-y)/3 -7y = 4

Explanation:

Solving the second equation for x, we get ...

3x = -17 -y . . . . subtract y

x = (-17 -y)/3 . . . divide by the x-coefficient

Substituting this for x in the first equation gives ...

2(-17-y)/3 -7y = 4

_____

Comment on this problem

If I were solving this by substitution, I'd substitute for y, not x. That way, fractions could be avoided.

User KlajdPaja
by
5.9k points